Bamboo Textiles: Natural and Chemical Fibers - E. P. Sem'ina (Теория и практика судебной экспертизы)
A classification of bamboo fibers is discussed, along with the appropriate use of relevant terminology and standardized notions. The paper presents the results of a study conducted on chemical bamboo-based fibers using microscopy (bright-field and polarized light microscopy), infrared spectroscopy (FTIR), and microchemical analysis. The findings show that manufactured fibers derived from bamboo using the viscose processing method are identified as viscose fibers. The term «bamboofibers» is only applicable to natural plant fibers extracted from bamboo culm